Evaluation of Hypertension Treatment in Patients Who Have Received mRNA-based Covid-19 Vaccines - apt Ainur Rizkiya (Eduvest - Journal of Universal Studies, 2026)
Hypertension remains one of the leading global public health problems and is a major risk factor for cardiovascular disease. The widespread implementation of COVID-19 vaccination, particularly mRNA-based vaccines, has raised concerns regarding potential cardiovascular effects, including transient blood pressure changes. This study aimed to evaluate hypertension treatment outcomes in patients who had received mRNA-based COVID-19 vaccines and to analyze the influence of sociodemographic factors on clinical outcomes. A quantitative analytic study with a retrospective cross-sectional design was conducted using electronic medical records from 400 adult hypertensive patients who received Pfizer or Moderna vaccines. Data included blood pressure measurements before and after vaccination, number of antihypertensive medications, comorbidities, and sociodemographic characteristics. Statistical analysis was performed using non-parametric tests. The results showed no statistically significant difference in the number of antihypertensive drugs before and after vaccination (median 2.00; p = 0.451). There were also no significant associations between sociodemographic variables and post-vaccination blood pressure, except a limited association with systolic blood pressure in patients with comorbidities. Overall, mRNA COVID-19 vaccination did not significantly affect antihypertensive therapy requirements or blood pressure control. These findings support the safety of mRNA vaccination in hypertensive patients, although continued monitoring, particularly of systolic blood pressure in patients with comorbid conditions, remains recommended.